Pragmatic Knowledge For Second Language Learners - Margana, Author: (English Education Department, Universitas Islam Indonesia, 2011)
To maximally acquire the target language, second language learners are demanded to master the knowledge of pragmatics on the grounds that it facilitates them to capture a comprehensive understanding of the classroom communication patterns which deal with how language is used according to its context. Added to this, knowledge of pragmatics can be used to minimize miscommunication and misunderstanding of the speech acts used in classroom communication practices. More specifically, second language learners have to acquire the issues of pragmatics which include types of illocutionary acts, illocutionary force, and implicatures. Such aspects of pragmatics are commonly found in classroom communication practices which are done by English teachers of secondary school levels. In reference to these issues, this paper attempts to review the types of illocutionary acts, illocutionary forces and conversational implicatures applied by English teachers of secondary school levels. Such an understanding of those three aspects of pragmatics is believed to facilitate students of secondary schools as the second language learners to easily make sense of the utterances as performed by English teachers in a series of English language teaching and learning practices.